2016
DOI: 10.1111/1750-3841.13362
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of In Vivo and In Vitro Assay Results for Assessment of Free Radical Scavenging Activity of Green Tea Nutraceuticals

Abstract: Green tea (GT)-derived catechins; epigallocatechin gallate (EGCG) in particular are commonly used nutraceuticals for their free-radical scavenging activity (FRSA). The influence of photodegradation on the protective power of GT nutracenticals against oxidative stress was thoroughly explored. Photodegradation of GT extracts was carried out and monitored using orthogonal stability-indicating testing protocol; in vitro and in vivo assays. Total polyphenol content (TPC) and FRSA were determined spectrophotometrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Dietary phenolic compounds as a special group of natural compounds have received enormous attention in recent years for their numerous bioactivities, such as anti‐inflammatory, anticancer, antioxidant, and antiallergenic activities (Beara and others ; Zhu and others ; Abd‐ElSalam and others ). They are broadly distributed in fruits, vegetables, tea leaves, and coffee beans (Kojima and others ; Harnly and others ).Therefore, incorporation of phenolic compounds into food materials is considered as an effective approach to enhancing antioxidant performance and bioactivity of food, including protein‐based food (Bartolomé and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary phenolic compounds as a special group of natural compounds have received enormous attention in recent years for their numerous bioactivities, such as anti‐inflammatory, anticancer, antioxidant, and antiallergenic activities (Beara and others ; Zhu and others ; Abd‐ElSalam and others ). They are broadly distributed in fruits, vegetables, tea leaves, and coffee beans (Kojima and others ; Harnly and others ).Therefore, incorporation of phenolic compounds into food materials is considered as an effective approach to enhancing antioxidant performance and bioactivity of food, including protein‐based food (Bartolomé and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Because these plant‐derived ingredients are rich sources of phytochemical antioxidants, they have great potential to protect the quality and nutritional value of meat products and possibly enhance the chemical safety as well. While the biological role of phytochemicals may be related to the self‐defense of plants—for example, resistance to pathogens and deterrence of predators—when tested in cell cultures and animals, many of them exhibit remarkable health‐promoting bioactivity, such as anti‐inflammation, anticancer, antioxidation, and antiallergenicity . For food and beverages, the antioxidant activity of phenolic compounds, apart from flavor and color, is of primary interest.…”
Section: Introductionmentioning
confidence: 99%
“…While the biological role of phytochemicals may be related to the self-defense of plants-for example, resistance to pathogens and deterrence of predators-when tested in cell cultures and animals, many of them exhibit remarkable health-promoting bioactivity, such as anti-inflammation, anticancer, antioxidation, and antiallergenicity. [8][9][10][11][12] For food and beverages, the antioxidant activity of phenolic compounds, apart from flavor and color, is of primary interest.…”
Section: Introductionmentioning
confidence: 99%
“…(14,27) In contrast, EGCg possesses free radical-scavenging activity and inhibits protein aggregation via proteasomal degradation. (31,32) Here, we determined how EGCg upregulates SMP30 expression. In fact, we found that EGCg can upregulate SMP30 expression even when cells are treated with CHX, an inhibitor of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%